Project Based Learning Model to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri Alue Ie Itam - Afriana, Lena; Darni (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning outcomes of sixth-grade students at Alue Ie Itam Public Elementary School on the topic of